Unidade de terapia intensiva : um estudo com filhos que possuem a mãe ou pai neste modo de internação - Lima, Fernanda de Azevedo (2011)
This dissertation aimed to investigate the experience and coping strategies of sons and daughters whose mother or father are hospitalized in an Intensive Care Unit. The study is divided in two parts: A theoretical paper, based on a bibliographic review of SCIELO, BIREME and PSYCHINFO databases. In such review, studies focusing on specific relatives were not found, except when it comes to parents whose babies are in Neonatal Intensive Care; there is a lack of investigations on coping strategies used by relatives in this situation and studies using both qualitative and quantitative methods were not found. Considering this, an empirical research was carried on focusing on such aspects, with a qualitative-quantitative approach. Participants were 30 sons or daughters of patients in ICU s. Chosen instruments were: a socio-demographic form; the Coping Strategies Inventory by Folkman and Lazarus (1985), adapted by Savóia and cols (1996); and a semi-structured interview. The Inventory allowed the identification of the following predominant coping strategies: Positive Reappraisal (97%); Social Support (93%) and Problem Solving (77%). Spearman correlation coefficients were estimated for the 66 questions on the Inventory and some variables: Religion presented negative correlation with item 51; Age above 50 presented positive and negative correlations with items 14 and 31, respectively; Education (university level) presented positive correlation with items 2 and 61 and negative correlation with items 25 and 32. There was an association between parenthood (sons with mothers in UCI) and questions 2, 3, 12, 25, 27, 34, 35 e 39. Despite that, it is not possible to stand that there is a significant positive or negative correlation among these variables and specific coping strategies. The following negative feelings where verified on the interviews: suffering, preoccupation, fear of death and shock; the fact that the patient spends most of the time alone is the biggest source of concern; the relatives routine is impaired due to the parent s hospitalization. Personal, spiritual and professional growth came out as positive reappraisal and participants were satisfied with the hospital staff attention regarding themselves and their parents. These results reinforce the need of a Life Quality Program for Relatives with parents in ICU, which could promote an opportunity to talk, listen and exchange experiences, including their fantasies regarding the ICU scenario, as well as coping strategies used during the period their parents are hospitalized